Morphological investigations on the circulus arteriosus cerebri in mole-rats (Spalax leucodon) - Aydin, A.; Yilmaz, S.; Ozkan, Z. E.; Ilgun, R. (Wiley-Blackwell, 2008)
The aim of the present study is to investigate the circulus arteriosus cerebri in mole-rats (Spalax leucodon). Six adult mole-rats were used for this purpose. Coloured latex was injected into the left ventriculus of the hearts of all the animals. After careful dissection, the circulus arteriosus cerebri (the circle of Willis) was investigated. The cerebrum and the cerebellum were supplied by the internal carotid- and the basilar arteries respectively forming the circulus arteriosus cerebri in mole-rats. In the investigated objects, the internal carotid- and the basilar arteries were not united directly and for this reason the circulus arteriosus cerebri was not formed completely in mole-rat. The branches supplying the medulla oblongata and the cerebellum originate from the basilar artery formed by union of the left and right vertebral arteries and the internal ophthalmic, the caudal cerebral, the choroid, the median cerebral, the rostral cerebral arteries originated from the internal carotid artery. After giving off the medial cerebral artery, the right and left rostral cerebral arteries on every two sides divided into the lateral and medial twin branches and by union of the lateral branches the internal ethmoidal artery, and by union of the medial branches, the ramus extending to facies medialis cerebri were formed. The ramus extending to the facies medialis cerebri was anastomosed with the branch of the caudal cerebral artery on the back of the corpus callosum. The last part of the basilar artery gave the two branches running toward the right and left side on the pontocrural groove (sulcus pontocruralis) and every one of these branches ramified into two rami. One of these rami formed into the rostral cerebellar artery and the other one extended to the tectum mesencephali. In conclusion, the arterial circle of the cerebrum and cerebellum was supplied by the internal carotid artery and the basilar artery respectively in mole-rats.